QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

The Literacy and Essential Skills Needs of Quebec's Anglophone Adults - Centre for Literacy (CFL) (2012)
Understanding the Literacy and Essential Skills Needs of Quebec’s Anglophone Adults,1 Phase 1, was a project designed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve Englishspeaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities (discussed in detail in Sections Three and Four) which showed large disparities in literacy performance among Quebec Anglophones (Corbeil 2006: 20). The findings suggested differences in needs from one community to another that may require targeted services.